2021
DOI: 10.3390/nano11051171
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Changes in Antioxidant Potential of Oakleaf Lettuce Seedlings Caused by Nano-TiO2 Treatment

Abstract: Nowadays, there is an increasing interest in nanoparticle (NP) technology used in household and industrial products. It could cause an accumulation and dispersion of NPs in the environment, with possible harmful effects on living organisms. Nanoparticles significantly affect plants and alter their physiology and biochemical pathways, and nanotechnology can be used to improve plant characteristics that are desirable by humans. Therefore, more extensive studies of NP interactions with plants are still needed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…To protect themselves from the effects of biotic or abiotic stress, plants maintain a balance by accumulating enzymatic and non-enzymatic components with a role in the defense system [40]. Studying the plants foliar treated with 0.75% suspension of TiO 2 NPs, it was found that the antioxidant activity initially increased in the treated plants compared to the control and then decreased [41].…”
Section: Determination Of Total Antioxidant Capacitymentioning
confidence: 99%
“…To protect themselves from the effects of biotic or abiotic stress, plants maintain a balance by accumulating enzymatic and non-enzymatic components with a role in the defense system [40]. Studying the plants foliar treated with 0.75% suspension of TiO 2 NPs, it was found that the antioxidant activity initially increased in the treated plants compared to the control and then decreased [41].…”
Section: Determination Of Total Antioxidant Capacitymentioning
confidence: 99%
“…Typically, lower concentrations of nTiO 2 are known to produce a positive impact on many plant functions [1] [14] while on the other hand, higher concentrations have been shown to produce a negative impact on plant growth [20] [25]. Furthermore, high concentrations of nTiO 2 can also lead to the production of oxidative stress and toxicity in plants due to their photocatalytic activity [26] [27] [28].…”
Section: Introductionmentioning
confidence: 99%